2022
DOI: 10.1111/bre.12721
|View full text |Cite
|
Sign up to set email alerts
|

Mesozoic–Cenozoic multistage tectonic evolution of the Pamir: Detrital fission‐track constraints from the Tajik Basin

Abstract: Knowledge of the tectonic history of the Pamir contributes to our understanding of both the evolution of collisional orogenic belts as well as factors controlling Central Asian aridification. It is, however, not easy to decipher the Mesozoic-Cenozoic tectonics of the Pamir due to extensive Neogene deformation in an orogen that remains largely understudied. This study reports detrital apatite and zircon fission-track (FT) ages from both the eastern Tajik Basin sedimentary rocks and Pamir modern river sands. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…You et al [28] reported that the concentration of peak age fluoclastic apatite fission tracks in the Daba Shan during the early Cenozoic occurred predominantly at 37 Ma (Figure 7(26)). The zircon and apatite fission-track ages near the source of the Hanjiang River constrain the timing of exhumation to 40 Ma [17] (Figure 7 (27)). The bedrock apatite fission-track and (U-Th)/He age confirm the exhumation of the western South Qinling Shan at (Figure 7 (28)).…”
Section: Cenozoic Exhumationmentioning
confidence: 99%
See 1 more Smart Citation
“…You et al [28] reported that the concentration of peak age fluoclastic apatite fission tracks in the Daba Shan during the early Cenozoic occurred predominantly at 37 Ma (Figure 7(26)). The zircon and apatite fission-track ages near the source of the Hanjiang River constrain the timing of exhumation to 40 Ma [17] (Figure 7 (27)). The bedrock apatite fission-track and (U-Th)/He age confirm the exhumation of the western South Qinling Shan at (Figure 7 (28)).…”
Section: Cenozoic Exhumationmentioning
confidence: 99%
“…The low-temperature thermochronological age of clastic sediments from rivers that flow in linear orogenic belts can provide more detailed information about the exhumation history of the orogenic belt [18][19][20][21]. This method has been extensively employed in the investigation of exhumation processes in linear orogenic belts, particularly the Alps in Europe [22][23][24], the Andes in South America [25], and the Tian Shan in Asia [26,27]. While conducting a modern fluvial apatite fission-track analysis on the tributaries of the Hanjiang River, You et al [28] primarily focused their study on the exhumation history of the Daba Shan, which is a branch of the Qinling Shan (Figure 2b).…”
Section: Introductionmentioning
confidence: 99%